2010
DOI: 10.1001/archinternmed.2010.92
|View full text |Cite
|
Sign up to set email alerts
|

Processes of Care Associated With Acute Stroke Outcomes

Abstract: Outcomes among patients with ischemic stroke or TIA can be improved by attention to swallowing function, DVT prophylaxis, and treatment of hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 28 publications
0
54
3
1
Order By: Relevance
“…We performed a secondary analysis of data derived from a retrospective cohort study that evaluated medical records through chart review of patients with an ischemic stroke or transient ischemic attack (TIA) admitted to one of two Department of Veterans Affairs (VA) or one of two non-VA hospitals between 1998 and 2003 [28]. We included veterans and nonveterans in the original parent study if they had an acute ischemic stroke or TIA, had neurological symptom onset within 2 days of admission, had a neurological deficit on admission (National Institutes of Health Stroke Scale [NIHSS] 2), and were 18 years old.…”
Section: Methodsmentioning
confidence: 99%
“…We performed a secondary analysis of data derived from a retrospective cohort study that evaluated medical records through chart review of patients with an ischemic stroke or transient ischemic attack (TIA) admitted to one of two Department of Veterans Affairs (VA) or one of two non-VA hospitals between 1998 and 2003 [28]. We included veterans and nonveterans in the original parent study if they had an acute ischemic stroke or TIA, had neurological symptom onset within 2 days of admission, had a neurological deficit on admission (National Institutes of Health Stroke Scale [NIHSS] 2), and were 18 years old.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found association between process of care performance measures and mortality outcomes for patients with cardiovascular disease and stroke. 30,31 It is certainly possible that improved guideline-based treatment, more frequent thrombolytic therapy, enhanced secondary prevention and risk factor management, early rehabilitation and patient education programs may also be responsible for the lower mortality rates among patients treated at stroke centers. However, these efforts may not have any appreciable shortterm or immediate life-saving effect, which is consistent with our findings of minimal mortality difference at day 1 and similar readmission rates at 30 days compared to greater survival benefit at the end of 1 year follow-up.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…(12) Briefly, this retrospective cohort included patients who were admitted with ischemic stroke or TIA at any of three VA or two non-VA hospitals, during the years 1998-2003, if they had a neurological symptom onset within 2 days of admission, had a neurological deficit on admission (rNIHSS ≥ 2), and were at least 18-years old. Patients were excluded from the QUEST study if they were residing in a skilled nursing facility at the time of stroke symptom onset, were already admitted to the hospital at the time of stroke symptom onset, were transferred from another acute care facility, or were not admitted to the hospital.…”
Section: Patients and Settingmentioning
confidence: 99%